(untitled) (Research, Society and Development, 2021)
In search of industrial growth, the dairy market seeks innovations such as the combination of alternative foods, resulting in new products, which are currently gaining consumer acceptance. In this context, the objective was to produce a Minas Padrão cheese, where coffee was added to the surface of the cheeses during the maturation process. The cheese was subjected to four treatments with coffee and water (Q2: 180g w / 3L; Q3: 210g w / 3L; Q4: 240g w / 3L; Q5: Bludge 200g w / ½L) and a control (Q1), for one period of 4 days with controlled temperature (4 ° C ± 1). After the immersion period, the cheeses were removed from the treatments and the maturation was maintained until completing 20 days and, subsequently, they were sensorially analyzed by 80 consumers who evaluated the acceptance and buying attitude of the new products. Using a 9-point hedonic scale, cheeses showed good acceptance, with no significant difference (p <0.05) for the attributes of aroma, color, consistency, flavor and overall appearance, except for appearance, with acceptability indexes (IA%) greater than 70%, with Q2 with the highest acceptance. Using a 5-point attitude scale to assess purchase intention, there were no significant differences (p <0.05), with their values above the indifference point (Q2: 4.40; Q3: 3.68; Q4: 3.57; Q5: 4.11). Therefore, the study demonstrates relevance in the new maturation process for Minas Padrão cheese and indicates Q2 cheese as a differentiated possibility for the dairy market.